Preferensi Oviposisi Nyamuk Aedes aegypti Terhadap Variasi Atraktan (Air Kotoran Sapi Dan Air Kotoran Ayam) - Hamsir Ahmad; Sulasmi; Aelizah Rahmasary (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2023)
One of the ways can be used to control mosquito vectors is using traps, namely egg traps (ovitrap). The trap will be filled with attractants as substances to attract female mosquitoes to come lay their eggs. Cow or chicken manure mixed with water is one of the ingredients which can be used as an attractant.This research aims to find out the oviposition preference of Aedes aegypti mosquitos to attractant variations (cow and chicken manure). The type of research used is an experiment with 3 replications and a variety of attractants. They are the mixture of water with cow and chicken manure with a concentration of 3% each. The observations were made for 7 days for each replication. The results show that the average number of trapped eggs varied in each medium. It was 145.6 in the cow manure, 55 in the chicken manure, and 25.6 in the control media. The results of statistical test show that the p value in cow manure was 0.013 <0.05 while the p value in chicken manure was 0.570 > 0.05.As a conclusion, there is a significant difference in the oviposition preferences of Aedes aegypti mosquitoes in the cow manure, and there is no significant difference in the oviposition preferences of Aedes aegypti mosquitoes in the chicken manure. The cow manure media is the main preference for Aedes aegypti mosquitoes to oviposition when compared to chicken manure media. It is suggested to the next research to carry out total egg hatchng and add various attractants. In addition, people also need to pay attention to environmental cleanliness to avoid mosquito breeding. Keywords : Attractant, Ovitrap, and Aedes aegypti.